Remaja Aktif Tanpa Rematik: Edukasi Pencegahan Rematik Dini di SMK Mahardika Batujajar - Theophylia Melisa Manumara; Zulfa Nursa'adah; Aqila Putri Rusdian; Ainiyah Athiasalwa; Zahrah Luthfiyani Fadillah; Alia Yunita; Nazwa Nepianti; Nazwa Cahaya Maulidha; Agustina Siti Lestari; Feby Febrina Asyfa Wahyuni; Wafa Alfi Fadilah (Jurnal Medika: Medika, 2026)
Rheumatism is an autoimmune disease that affects the joints and can cause pain, swelling, joint stiffness, and limited mobility if not properly managed. Adolescents’ lack of knowledge about rheumatism leads to low awareness of the importance of maintaining joint health from an early age. Health education serves as a promotive and preventive measure to enhance adolescents’ knowledge of rheumatism and the importance of maintaining physical health and a strong immune system. This health education activity was conducted at SMK Mahardika Batujajar, targeting 24 students in the 10th-grade PPLG 3 class. The method used was a quasi-experimental design with a pretest-posttest approach. The activity was carried out through health counseling using PowerPoint presentations, leaflets, educational posters, and interactive question-and-answer sessions. Evaluation was conducted using pretest and posttest questionnaires to determine the increase in students’ knowledge before and after the health education session. The results of the activity showed an increase in students’ knowledge regarding the definition of rheumatism, risk factors, signs and symptoms, as well as prevention efforts for rheumatism. Before receiving health education, most students still had a limited understanding of rheumatism and its connection to the immune system. After receiving health education, students were able to understand the importance of maintaining joint health and adopting a healthy lifestyle starting in adolescence. Health education on rheumatism has been shown to be effective in increasing students’ knowledge and awareness of the importance of maintaining a healthy immune system and joint health.